2020
DOI: 10.1007/s11096-020-01075-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-dispensing pharmacist integrated in the primary care team: effect on the quality of physician’s prescribing, a non-randomised comparative study

Abstract: Background Especially in elderly with polypharmacy, medication can do harm. Clinical pharmacists integrated in primary care teams might improve quality of pharmaceutical care. Objective To assess the effect of non-dispensing clinical pharmacists integrated in primary care teams on general practitioners’ prescribing quality. Setting This study was conducted in 25 primary care practices in the Netherlands. Methods Non-randomised, controlled, multi-centre, complex intervention study with pre-post comparison. Firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…11,46,47 However, the T A B L E 1 Characteristics (matching criteria and mean number of PIMs per hospital stay) in the exposed and unexposed cohorts data from nonrandomized studies of the effects of medication reviews are discordant. [48][49][50] In the study of primary care by Sloeserwij et al, a medication review by a nondispensing pharmacist did not improve most of the prescription quality indicators. The researchers suggested that "prescribing indicators might not capture the full effect of nondispensing pharmacists integrated in primary care teams, when interventions are not specifically targeted upon these indicators".…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…11,46,47 However, the T A B L E 1 Characteristics (matching criteria and mean number of PIMs per hospital stay) in the exposed and unexposed cohorts data from nonrandomized studies of the effects of medication reviews are discordant. [48][49][50] In the study of primary care by Sloeserwij et al, a medication review by a nondispensing pharmacist did not improve most of the prescription quality indicators. The researchers suggested that "prescribing indicators might not capture the full effect of nondispensing pharmacists integrated in primary care teams, when interventions are not specifically targeted upon these indicators".…”
Section: Discussionmentioning
confidence: 94%
“…Many studies (including a number of RCTs) have shown that medication reviews can reduce the number of PIMs 11,46,47 . However, the data from nonrandomized studies of the effects of medication reviews are discordant 48–50 . In the study of primary care by Sloeserwij et al, a medication review by a nondispensing pharmacist did not improve most of the prescription quality indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also looked at drug burden index, direct healthcare costs and the quality of prescribing (measured via prescribing quality indicators) but here no differences were found with usual care [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Next to i.e. confidence in the collaborations’ benefits and good communication, they found that close proximity between professions positively affects collaboration, medication management [ 17 , 37 , 38 ], and monitoring [ 39 ].On the other hand, factors impeding collaboration are i.e. lack of clarity regarding each other’s roles and responsibilities, lack of trust, respect, and time [ 36 ].…”
Section: Discussionmentioning
confidence: 99%